Effects of FSHR and FSHB Variants on Hormonal Profile and Reproductive Outcomes of Infertile Women With Endometriosis - Bianco, Bianca; Loureiro, Flavia Altheman; Trevisan, Camila Martins; Peluso, Carla; Christofolini, Denise Maria; Montagna, Erik; Laganà, Antonio Simone; Barbosa, Caio Parente (Frontiers in Endocrinology, 2021)
Background: Single nucleotide variants (SNVs) FSHB:c.-211G>T, FSHR:c.919G>A, and FSHR:c.2039G>A were reported to be associated with the variability in FSH and LH levels, and in vitro fertilization (IVF) outcomes. In this study, we aimed to evaluate the effects of FSHB:c.-211G>T, FSHR:c.919G>A, and FSHR:c.2039G>A variants, alone and combined, on the hormonal profile and reproduction outcomes of women with endometriosis. Methods: A cross-sectional study was performed comprising 213 infertile Brazilian women with endometriosis who underwent IVF treatment. Genotyping was performed using TaqMan real-time PCR. Variables were compared according to the genotypes of each variant and genetic models, and the combined effects of the SNVs were evaluated using the multifactorial dimensionality reduction method. Results: FSHB:c.-211G>T affected LH levels in women with overall endometriosis and minimal/mild disease. FSHR:c.919G>A affected FSH levels in women with overall endometriosis and the number of oocytes retrieved in those with moderate/severe endometriosis. Moreover, the FSHR:c.2039G>A affected FSH levels in women with overall endometriosis, LH levels and total amount of rFSH in those with minimal/mild disease, and number of follicles and number of oocytes retrieved in those with moderate/severe endometriosis. No effect on hormone profile or reproductive outcomes was observed when the genotypes were combined. Conclusions: Variants of the FSHB and FSHR genes separately interfered with the hormonal profiles and IVF outcomes of women with endometriosis.